Changes in unprofessional behaviour, teamwork and co‐operation among hospital staff during the COVID‐19 pandemic. Issue 10 (14th September 2022) - Westbrook, Johanna I.; McMullan, Ryan; Urwin, Rachel; Churruca, Kate; Metri, Joelle; Loh, Erwin; Li, Ling
Abstract: A survey administered to staff at five hospitals investigated changes in unprofessional behaviour, teamwork and co‐operation during the COVID‐19 pandemic. From 1583 responses, 76.1% (95% confidence interval (CI): 74.0–78.2%) reported no change or a decrease in unprofessional behaviours. Across all professional groups, 43.6% ( n  = 579, 95% CI: 41.0–46.3%) reported improvements in teamwork and co‐operation. Findings suggest that intensifying work demands, such as those resulting from the pandemic, are not a major trigger for unprofessional behaviour, and root causes lie elsewhere.